PENGARUH MANAJEMEN KONFLIK TERHADAP KINERJA GURU SEKOLAH DASAR DI GUGUS MAWAR METRO PUSAT - Selli Oftiah, Riswandi; Siti Nurjanah, Muhammad Nurwahidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this study was the less than optimal performance of teachers. This study aimed to determine the effect of conflict management on the performance of elementary school teachers in the Gugus Mawar Metro Pusat. The data collection technique used a questionnaire. The sampling technique used in this study used Probability Sampling technique, namely Simple Random Sampling. The population in this study were elementary school teachers in the Mawar cluster in Metro Pusat, Metro City, totaling 78 people in the 2024/2025 academic year. Determination of the sample using the slovin formula amounted to 65 respondents. The research approach was quantitative research with the type of research using ex post facto. The data analysis technique used is simple linear regression test. The results of the simple linear regression test showed that the square regression coefficient value was 0.622 and the significance value is 0.000 <0.05. The conclusion is that there was a positive and significant effect on conflict management on teacher performance.